Getting physical : the rise of fitness culture in America - McKenzie, Shelly (Culture America., 2013)
"In this first book on the modern history of exercise in America, Shelly McKenzie chronicles the governmental, scientific, commercial, and cultural forces that united--sometimes unintentionally--to make exercise an all-American habit. She tracks the development of a new industry that gentrified exercise and made the pursuit of fitness the hallmark of a middle-class lifestyle. Along the way she scrutinizes a number of widely held beliefs about Americans and their exercise routines, such as the link between diet and exercise and the importance of workplace fitness programs."--